2016
DOI: 10.1002/app.43825
|View full text |Cite
|
Sign up to set email alerts
|

Re‐entrant transition of aluminum‐crosslinked partially hydrolyzed polyacrylamide in a high salinity solvent by rheology and NMR

Abstract: Linked polymer solution (LPS) is a nanoparticle polymer and designed by crosslinking a high molecular weight partially hydrolyzed polyacrylamide (HPAM) with aluminum (III). It has been applied in the oil industry to enhance oil recovery by improving sweep efficiency and by microscopic diversion in porous media. To achieve good propagation properties, aggregates formed by intermolecular crosslinking and gel formation should be avoided. To our knowledge, there is no established method to distinguish between intr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…In Sikora and McBride's article [44,45], they found that ultraviolet spectrophotometry can provide valuable information on the composition and stability constant of a metal-ligand complex, and then they studied the ultraviolet spectrogram of aluminum complex, which had the maximum absorption peak in a certain band. In Kedir et al's article [25,26,32] UVÀvisible spectroscopy was used for investigating the phase transition of LPS. On the basis of the principles, the absorption curves of the three aluminum citrates, which are prepared with deionized water and measured by UV-VIS spectrophotometer, are shown in Figure 2.…”
Section: The Basic Principle Of Experimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…In Sikora and McBride's article [44,45], they found that ultraviolet spectrophotometry can provide valuable information on the composition and stability constant of a metal-ligand complex, and then they studied the ultraviolet spectrogram of aluminum complex, which had the maximum absorption peak in a certain band. In Kedir et al's article [25,26,32] UVÀvisible spectroscopy was used for investigating the phase transition of LPS. On the basis of the principles, the absorption curves of the three aluminum citrates, which are prepared with deionized water and measured by UV-VIS spectrophotometer, are shown in Figure 2.…”
Section: The Basic Principle Of Experimentsmentioning
confidence: 99%
“…The first step is the transition from a random polymer coil to structured coils, the second step is that the networked weak gel is formed by coil aggregates above the threshold concentration. In 2016, Kedir et al [26] found that Linked Polymer Solution (LPS) solution at a high salinity solvent underwent a phase transition by chain re-expansion, called reentrant transition, of which the rate is affected by the concentrations of Al 3+ . The above literature can provide a basis for us to better understand the reaction mechanism of HPAM/Al 3+ .…”
Section: Introductionmentioning
confidence: 99%
“…The most widely used polymer profile modification systems mainly include polyacrylamide (PAM) and partially hydrolyzed PAM (HPAM). These systems can be divided into inorganically crosslinked [using Cr­(III), Al­(III), and Zr­(IV) polyvalent metal ions as crosslinkers to form three-dimensional (3D) network gel structures through ionic bonding] and organically crosslinked (using phenol-formaldehyde, polyethyleneimine, hydroquinone (HQ), and hexamethylenetetramine as crosslinkers to form 3D network gel structures through covalent bonding) gel systems. In addition, an acrylamide monomer (AM) can form a composite hydrogel with nanocellulose or nano fly ash through free radical polymerization, improving the gel performance, and is used for oilfield profile modification. Organically crosslinked polymer gels are formed by intermolecular reactions and have higher thermal stability owing to covalent bonds with higher bond energies than ionic bonds. , However, when subjected to high temperature and salinity, the amide groups (−CONH 2 ) on polymer molecular chains can hydrolyze to form carboxyl groups (−COOH) to become HPAM, which can form ionic bonds with polyvalent metal ions and cause dehydration. Therefore, applications of conventional polymer gels for EOR are restricted as most of the polymer gels cannot withstand high temperature and salinity and restrict the recovery. Zhu et al , developed a terpolymer gel system formed by organic crosslinkers (phenol, resorcinol, catechol, and HQ).…”
Section: Introductionmentioning
confidence: 99%